Development Of Ecopedagogy Based Module To Optimize Pancasila Student Profile At SDN Sangen 01 Madiun - Salsabila Rona Azizah; Raden Syaifuddin; Sri Utami (UNIVERSITAS PGRI MADIUN, 2025)
This study discusses the Development of Ecopedagogy Based Modules to Optimize Pancasila Student Profiles at JHS Sangen 01 Madiun. This study uses the Borg and Gall development with 10 stages, but in this study it only uses up to stage 8. Ecopedagogy-based modules must meet valid, effective and practical criteria. The results of the validity test with 3 validators obtained a result of 88.6 with a very decent category. The results of product effectiveness as seen from the achievement of learning outcomes and testing using independent sampling t-tests obtained results (6.687 > 1.708), so that the ecopedagogy-based module was declared effective. Relative effectiveness obtained results of 59.11% have a medium effectiveness category. The results of the practicality of ecopedagogy-based modules using student response questionnaires obtained 90.16% results which were considered very practical.